An Analysis of the Causes of Relapse Among Individuals with Substance Abuse - Pathak, Dhanush Chandra (NPRC Journal of Multidisciplinary Research, 2026)
Background: Relapse into drug abuse is a major challenge in Nepal, up to 75% of individuals relapse within six months after completing treatment. Many individuals who undergo treatment return to substance use due to a variety of psychological, soc-economic, and use of treatment approach. This study addresses a significant public health issue, substance misuse relapse in the specific context of rehabilitation centers in Birendranagar, Surkhet, Nepal. The present study aimed identify the key factors contributing to relapse among individuals with substance abuses.Methods: This study employed a descriptive research design with a quantitative approach. A survey method was used, and primary data were collected through structured questionnaires. Data were collected in the year of 2025 from six rehabilitation centers located in Birendranagar municipality, Surkhet. Out of the total population of 175 members from six rehabilitation centers,120 respondents were selected. The sample size was determined using Yamane’s (1967) formula at a 5% margin of error, the sample size was calculated to be 122. However, 120 respondents were selected using simple random sampling.Findings: The study revealed that the majority of respondents (86.67%) cited personal choice as the main cause, 40% said that social events frequently led to relapses, 75.83% said that arguments with friends or family were significant contributing factors, 50.83% cited financial stress and 45% mentioned work-related stress as significant causes, and 49.17% acknowledged that social media or online triggers frequently affected them. The majority of (77.50%) responded using of western treatment models, rather than locally adapted approaches in the rehabilitation centers may contribute significantly to relapse.Conclusion: The result demonstrated several key causes of relapse including family and peer conflict, financial problem, lack of motivation, work-related stress, health issues, social media and use of western treatment models rather than local approaches in a rehabilitation center.Novelty: This study contributes new insights into the causes of relapse by examining both social and structural factors among individuals in rehabilitation centers. It highlights the influence of family conflict, and social media. Although various studies (National Institute on Drug Abuse, 2018);(Devi & Singh, 2023); (Adem et al., 2025); (Araban et al., 2026); (Ibrahim & Kumar, 2009);(Amat et al., 2020);(Domino, 2005);(Abdullah et al., 2020);(Sinha, 2011);(Lian & Chu, 2013) claimed about various causes and effects of  relapse but mismatch between western treatment models and local approaches, as a causes of relapse with substance abuses, which has received limited or no attention in the previous studies.